2020
DOI: 10.1002/jmv.26258
|View full text |Cite
|
Sign up to set email alerts
|

Deep throat saliva as an alternative diagnostic specimen type for the detection of SARS‐CoV‐2

Abstract: Nasopharyngeal swabs (NPS) are widely accepted as specimens for the detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in the current pandemic of coronavirus disease 2019. However, the collection procedures for NPS specimens causes sneezing and coughing in most patients, which generate droplets or aerosol particles that are hazardous to the healthcare workers collecting these specimens. In this study, 95 patient‐matched paired deep throat saliva (DTS) and NPS specimens from 62 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 8 publications
3
82
0
3
Order By: Relevance
“…No randomized controlled clinical trial was found. All manuscripts included were cross-sectional or cohort studies [ 6 , 7 , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ] ( Table A.1 , Table A.2 , Table A.3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No randomized controlled clinical trial was found. All manuscripts included were cross-sectional or cohort studies [ 6 , 7 , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ] ( Table A.1 , Table A.2 , Table A.3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In samples whose posterior oropharyngeal saliva is collected, other secretions are added besides the saliva that is secreted by larger or smaller salivary glands, which may come from the upper or lower respiratory tract and gingival fluid [ 7 , 55 ]. All studies that used this collection method demonstrated good performance in SARS-CoV-2 detection, including asymptomatic and pre-symptomatic infections [ 7 , 13 , 21 , 23 , 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of deep-throat saliva, which is the self-collection of the posterior oropharyngeal secretion, was particularly studied in depth. The sensitivity is comparable to nasopharyngeal swab specimens [ 13 , 16 , 28 ]. As the result of heterogeneity of methods and study designs, the WHO do not currently recommend the use of saliva as the sole specimen type for clinical diagnosis of COVID-19 infection [ 4 ].…”
Section: Specimen Typesmentioning
confidence: 99%
“…(3)(4)(5) Several studies have investigated the use of saliva as a specimen for testing for SARS-CoV-2 with mixed results. (3,(5)(6)(7)(8)(9)(10)(11) We, therefore, undertook a direct NPS to saliva specimen comparison to provide further clarification regarding the use of saliva as a potential specimen for testing.…”
Section: Introductionmentioning
confidence: 99%